Methodological principles of creating ethnic design architectural environment - Arbyzov, V. (Theory and practice of design, 2016)
The article defined methodological principles of creating ethnic design architectural environment with the determination of hierarchical levels of its manifestations and attributes. According to them examined system-structural components of forming and development of architectural environment, taking into account national culture and identity.